The Relationship of Slavisms and Hybrids in Konstantinas Sirvydas’s Dictionarium trium linguarum (1642) and Promptuarium dictionum Polonicarum, Latinarum et Lituanicarum (1620) - Smetonienė, Anželika (Senoji Lietuvos literatūra, 2025)
The article examines the borrowed lexical elements in Konstantinas Sirvydas’s Promptuarium dictionum Polonicarum, Latinarum et Lituanicarum of 1620 (hereinafter SPr) and the dictionary Dictionarium trium linguarum of 1642 (hereinafter SD). A total of 955 unique Slavisms and hybrids with Slavic roots were selected from SPr and SD, of which 571 words were recorded in SPr and 703 in SD. Among the 703 words attested in SD, 185 Slavisms and hybrids are not only absent from SPr but also lack any common root words in it. These particular loanwords are the focus of this study. The aim was to determine their relationship with SPr and to explore possible reasons why certain Slavisms and hybrids were not used in the earlier dictionary but were recorded in the later one. Among the common Slavisms and hybrids used in SD but not found in the SPr, there is a group of words that are not found in SPr due to the fact that the only surviving copy of the Promptuarium is defective, i.e., some pages are missing; today, it is not possible to check the translation of some of the words and to make comparisons with SD (e.g., Pol. bęben / Lith. būbnas SD 9 / Lith. ? SPr). This group represents 22.7 per cent of the words under investigation. The remaining headwords, for which Slavisms or hybrids were used in translations in SD, can be compared with the corresponding entries in SPr. One group (4.3 per cent) consists of cases where corresponding headwords are present in SPr but are provided without a Lithuanian translation, e.g., Pol. kołacz / Lith. karvojus SD 111 // Pol. kołacz / Lith. – SPr 59. A significant number of Slavisms and hybrids found only in SD (59.5 per cent) are absent from the earlier source due to differences in the lexical registers of the dictionaries of 1620 and 1642. This is the largest portion of the material analysed in this article. Such a high percentage can be explained by the fact that SD is a more extensive work containing a larger number of Polish word combinations, which required the use of loanwords or hybrids in translation. Of the Slavisms and hybrids examined in SD, 13.6 per cent could be compared within the corresponding headword entries in both SD and SPr. A noticeable tendency is that SD omits Slavisms and hybrids that are formally identical to Polish headwords (e.g., Pol. katowanie / Lith. baudimas / buzavojimas SD 99 / Lith. kotavojimas SPr 51). However, more than half of these 13.6 per cent of cases involve instances where SPr uses native Lithuanian words, whereas in SD, Slavisms and hybrids appear instead.